Product market deregulation and employment outcomes: Evidence from the German retail sector - Charlotte Senftleben-König (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
This paper investigates the short- and medium-term effects of the deregulation of shopopening hours legislation on retail employment in Germany. In 2006, the legislative competence was shifted from the federal to the state level, leading to a gradual deregulation of shop opening restrictions in most of Germany's sixteen federal states. The paper exploits regional variation in the legislation in order to identify the effect product market deregulation has on retail employment. We find robust evidence that the deregulation of shop closing legislation had negative effects on retail employment, with considerable heterogeneity in terms of the type of employment as well as establishment size. That is, the employment losses are most pronounced for small retail stores and are almost exclusively borne by full-time employees.
Keywords: J21; L51; L81; 330; Product market regulation; Employment; Retail trade